Apego y adopción. - Apolo Orellana, Evelyn Lisseth (2015)
This paper case study of the need to address the issue of addiction and adoption. The objective of this research is to determine the type of attachment of an adoptive family, from a psychoanalytic view and the results achieved are able to determine that there is a child ambivalent insecure attachment to his adoptive mother, through the development of the libido It will symbolically organizing the psyche of the child who perceives the mother or caregiver attachment figure as satisfying their basic needs. Taking these principles raises Bowlby attachment theory, establishing safe avoidant attachment type ambivalent anxious and eager. In the first chapter the generality of the object of study is presented, defining and contextualizing the object established facts of interest and ultimate target of the investigation, in chapter two epistemological theoretical foundation of the study sample chapter three corresponds to the process methodology that was used and finally in the fourth chapter discussing the research results indicated. The research raised responds to a qualitative approach and the biographical, analytical and inductive methods, which together with clinical techniques such as interview, psychometric and projective allow develop the life history of the child evaluated. The Test of the Family and Panasn questionnaire, show the child their emotional voids generated from rejection and abandonment of her birth mother, and require that this family resort to psychotherapeutic processes, to develop their losses and improve attachment level. In children adopted the experiences of neglect and abuse are issues that negatively affect the construction of safe bonding, generating new forms of addiction.